META-SINTESIS: PEMBELAJARAN MATEMATIKA BERBANTUAN GEOGEBRA UNTUK MENINGKATKAN KEMAMPUAN HOTS - Tuti Haryati (Jurnal Dimensi Matematika, 2022)
This study aims to reanalyze the GeoGebra-assisted mathematics learning in improving students' High Order Thinking Skills. In addition, this article also discusses the ability of teachers and students with HOTS abilities to learn mathematics without the help of GeoGebra. GeoGebra is used to help teach and learn mathematics to make it easier for students to understand and construct the material. The method used in this research is meta-synthesis as a qualitative systematic review by analyzing ten journals relevant to the research title. The first step is to formulate the research problem, then proceed with tracing the existing studies that are relevant to the research title which will then be analyzed in depth. The data collection technique used non-test by reviewing previous research with similar problems to obtain results and conclusions. The journals analyzed in this study were ten nationally accredited journals that discussed GeoGebra-assisted mathematics learning and HOTS. The results of the analysis of ten related journals concluded that GeoGebra-supported math learning can improve the skills of HOTS students. Teachers must improve their understanding of HOTS and the need for training in designing lesson plans and making HOTS questions for teachers and students.